Analisis Penggunaan Alat Panen Padi Modern dan Tradisional Terhadap Tingkat Produksi Padi di Kecamatan Bolyohuto Kabupaten Gorontalo - Asriyanti, Asriyanti; Olilingo, Fahrudin Zain; Yulia, Fitri Hadi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Gorontalo Province is one of the regions on Sulawesi Island that has excellent potential in the agricultural sector, particularly in rice commodities, which play an important role in maintaining food security both at the regional and national levels. Boliyohuto District, located in Gorontalo Regency, is one of the centers of rice production with varied harvesting practices—some farmers still use traditional methods, while others have adopted modern harvesting technology. This research was conducted to compare the effectiveness of using modern and traditional harvesting tools in terms of production results, operational costs, and farmers’ income in the area. Through a quantitative approach using regression analysis, the results of the study indicate that the use of modern harvesting tools has a significant positive effect on work efficiency, crop yield, and farmers’ income. Modern harvesting technology allows the harvesting process to be carried out more quickly, saves labor, and minimizes yield losses compared to traditional methods. Conversely, farmers who still use traditional methods face limitations in terms of time, labor, and productivity. These differences confirm that the implementation of agricultural mechanization plays an important role in increasing productivity as well as improving the welfare of farmers in Boliyohuto District. The findings of this study emphasize the importance of local government support through the provision of agricultural facilities, technical training, and subsidy policies for harvesting tools so that farmers can adapt to developments in agricultural technology. With the implementation of more efficient and sustainable harvesting technologies, the agricultural sector in Gorontalo Province is expected to continue to grow and strengthen food security at both regional and national levels.